Description of Diploplastron dehorityi sp. nov. (Entodiniomorphida, Ophryoscolecidae), a new rumen ciliate from Brazilian sheep (Ovis aries) - Cedrola, Franciane; Dias, Roberto Júnio Pedroso; Martinele, Isabel; D’agosto, Marta (Zootaxa, 2017)
To date the genus Diploplastron comprised only one species of ophryoscolecid ciliate, Diploplastron affine, which is characterized by having two retractable ciliary zones in the anterior end of the body, two slender and juxtaposed skeletal plates on the right side, a rod shape macronucleus, and two contractile vacuoles. During study on the characterization of rumen ciliate community composition in Brazilian domestic sheep, we observed ciliates with atypical morphology but with diagnostic features of genus Diploplastron. This study describes Diploplastron dehorityi, a new species of ophryoscolecid ciliate, that differs from D. affine, primarily, in the morphology of skeletal plates, morphology of nuclear apparatus and body shape. In addition to the similarities between the new species and congener species, D. dehorityi has some morphological similarities to species of genus Eremoplastron.